Determinant Factor on Stock Price Food and Beverages Industry Sector - Kusdianto, Kemas Dedy; Siswanti, Indra (Accounting Department,, 2022)
Purpose -This study aims to test the effect of leverage and firm size on stock price with return on owner equity as an intervening variable and managerial experiences as moderating variables. Design/methodology/approach—This study uses secondary data in the form of company financial statements from 2016 to 2020. The population is 49 consumer goods companies, and the sample is 29 companies. The data processing method used is warp PLS. Findings- The results of the study state that 1) Leverage has a significant effect on ROE; 2) Company size has a significant effect on ROE; 3) Leverage has no significant effect on stock prices; 4) Firms size has a significant effect on stock prices; 5) ROE has a significant effect on stock prices; 6) ROE is mediated effect Leverage on Stock Prices; 7) ROE is mediated effect Firms Size on Stock Prices; 8) Managerial experience is moderating effect Leverage on ROE; 9) Managerial experience is moderating effect Firms Size on ROE. Practical implications—This research has implications for companies where it is important to consider investment managers' experience when making decisions. Originality/value—This study uses a consumer goods company as the subject of research. The research is expected to assist the company in making a decision related to a manager's experience that can affect stock prices. Keywords- Leverage, Firms Size, Return On Owners Equity, Stock Price, Managerial Experiences. Paper type — Case study